The new generation of search engines based on natural language processing - Pérez-Agí¼era, José-Ramón (Anuario ThinkEPI, 2008)
Current trends in natural language processing and information retrieval are briefly analysed to show their impace on the search engine market. Powerset and Hakia are highlighted as the main agents of this change.